FIGO good clinical practice paper: management of the second stage of labor. Issue 2 (28th January 2021) - Wright, Alison; Nassar, Anwar H.; Visser, Gerry; Ramasauskaite, Diana; Theron, Gerhard
Abstract: This good clinical practice paper provides an overview of the current evidence around second stage care, highlighting the challenges and the importance of maintaining high‐quality, safe, and respectful care in all settings. It includes a series of recommendations based on best available evidence regarding length of second stage, judicious use of episiotomy, and the importance of competent attendants and adequate resource to facilitate all aspects of second stage management, from physiological birth to assisted vaginal delivery and cesarean at full dilatation. The second stage of labor is potentially the most dangerous time for the baby and can have significant consequences for the mother, including death or severe perineal trauma or fistula, especially where there are failures to recognize and repair. This paper sets out principles of care, including the vital role of skilled birth attendants and birth companions, and the importance of obstetricians and midwives working together effectively and speaking with one voice, whether to women or to policy makers. The optimization of high‐quality, safe, and personalized care in the second stage of labor for all women globally can only be achieved by appropriate attention to the training of birth attendants, midwives, and obstetricians. FIGO is committed to this aim alongside the WHO, ICM, and all FIGO's 132 member societies. Abstract : This paper provides an overview of the current evidence in best practice for second stage care, highlighting the challenges of maintaining high‐quality, safe, and respectful care in all settings.